THE IMPORTANCE OF ECONOMIC STRUCTURE EVOLUTION IN ACHIEVING PERFORMANCE - FROM AGRARIAN ECONOMY TO COMPETITIVENESS IN ROMANIAN ECONOMY - Jean Vasile, Andrei; Ungureanu, Adrian (Economics of Agriculture, 2014)
In terms of more increased integration and globalization of markets, risk diversification and exposure to external economic factors disturbing the structure of the national economy acquires a major role in alleviating and absorbing adverse effects on national economies are exposed. Starting from the reality that reducing disparities and achieving convergence criteria cannot be achieved except through the perspective of economic structures, the main objective of this research is the analysis of the importance of the economic structure in achieving functional requirements and competitive market economy, in the process of transition agrarian economy to a market economy in Romania, highlighting the main changes and effects that occurred in the past twenty-three years in the national economy, with a closer approach on agricultural structures.